Climate change, freshwater ecosystems and inland fisheries: implications for the developing nations - Biju Kumar, A. (Hawassa University, 2020)
Freshwater ecosystems are vital for ensuring drinking water supplies, bio-resources that support livelihood, and a wide array of ecosystem services. Further, they are among the key components in achieving the United Nations Sustainable Development Goals (UN SDGs) set for the year 2030, including poverty reduction, food security, clean water and sanitation, conservation of biodiversity and climate action. The aquatic ecosystems globally are susceptible to the impacts of climate change much more than terrestrial and marine ecosystems, impacting the livelihood of fishers and farmers depending on it. Climate change is expected to adversely affect the sustainable development capabilities of many Asian and African nations by putting more pressures on natural resources and the environment. This article reviews the impact of climate change on freshwater ecosystems and fisheries and addresses the key adaptation, mitigation and management strategies to address the issue of climate change.